Platelets in Critical Illness - Levi, Marcel (Seminars in Thrombosis and Hemostasis, 2016)
In patients with critical illness, thrombocytopenia is a frequent laboratory abnormality. However frequent this may occur, a low platelet count is not an epiphenomenon, but a marker with further significance. It is always important to assess the proper cause for thrombocytopenia in critically ill patients because different underlying disorders may precipitate different diagnostic and therapeutic management strategies. Platelets are part of the first-line defense of the body against bleeding; hence, thrombocytopenia may increase the risk of hemorrhage. In case of systemic inflammatory syndromes, such as the response to sepsis, disseminated intravascular platelet activation may occur. This will contribute to microvascular failure and thereby play a role in the development of organ dysfunction. Platelets are circulating blood cells that will normally not interact with the intact vessel wall but that may swiftly respond to endothelial disruption (which is often part of the pathogenesis of critical illness) by adhering to subendothelial structures, followed by interaction with each other, thereby forming a platelet aggregate. The activated platelet (phospholipid) membrane may form a suitable surface on which further coagulation activation may occur. A low platelet count is a strong and independent predictor of an adverse outcome in critically ill patients, thereby facilitating a simple and practically risk assessment in these patients and potentially guiding the use of complex or expensive treatment strategies.
Keywords: platelets; coagulation; intensive care; sepsis; disseminated intravascular coagulation; thrombotic microangiopathy; immune thrombocytopenia